Activation of G protein coupled estrogen receptor (GPER) promotes the migration of renal cell carcinoma via the PI3K/AKT/MMP-9 signals. Issue 2 (4th March 2018) - Guan, Bao-zhang; Yan, Rui-ling; Huang, Jian-Wei; Li, Fo-Lan; Zhong, Ying-Xue; Chen, Yu; Liu, Fan-Na; Hu, Bo; Huang, Si-Bo; Yin, Liang-Hong
Abstract : Renal cell carcinoma (RCC) is the third most frequent malignancy within urological oncology. However, the mechanisms responsible for RCC metastasis are still needed further illustration. Our present study revealed that a seven-transmembrane receptor G-protein coupled estrogen receptor (GPER) was highly detected in various RCC cell lines such as ACHN, OS-RC-2 and SW839. The activation of GPER by its specific agonist G-1 significantly promoted the in vitro migration and invasion of ACHN and OS-RC-2 cells. G-1 also up regulated the expression of matrix metalloproteinase-2 (MMP-2) and MMP-9. The inhibitor of MMP-9 (Cat-444278), but not MMP-2 (Sc-204092), abolished G-1 induced cell migration, which suggested that MMP-9 is the key molecule mediating G-1 induced RCC progression. Further, G-1 treatment resulted in phosphorylation of AKT and ERK in RCC cells. PI3K/AKT inhibitor (LY294002), while not ERK inhibitor (PD98059), significantly abolished G-1 induced up regulation of MMP-9 in both AHCN and OS-RC-2 cells. Generally, our data revealed that activation of GPER by its specific agonist G-1 promoted the metastasis of RCC cells through PI3K/AKT/MMP-9 signals, which might be a promising new target for drug discovery of RCC patients.